Association between the ACE I/D polymorphism and physical activity in Polish women - Cięszczyk, Paweł; Jastrzębski, Zbigniew; Zarębska, Aleksandra; Sawczyn, Michał; Drobnik-Kozakiewicz, Izabela; Leońska-Duniec, Agata; Żmijewski, Piotr; Murawska-Ciałowicz, Eugenia; Petr, Miroslav; Contrò, Valentina; Proia, Patrizia; Zaremba, Aneta; et al. (Akademia Wychowania Fizycznego w Poznaniu)
Angiotensin converting enzyme gene (ACE) is the most frequently investigated genetic marker in the context of genetic conditioning of athletic predispositions. However, the knowledge of ACE’s potential modifying effect on changes in selected body traits achieved through a training programme is still limited. Therefore, we have decided to check whether selected body mass, body composition variables, oxygen uptake parameters as well as strength/speed parameters observed in physically active participants will be modulated by the ACE I/D polymorphism. The genotype distribution was examined in a group of 201 young healthy women measured for chosen traits before and after the completion of a 12-week moderate-intensive aerobic training programme. Our results revealed the significant genotype × training interactions for VEmax and power of countermovement jump, whereas training improvements were demonstrated for almost all parameters. In addition, main effects of the ACE I/D genotype on TGL, HDL, glucose and 10 m run were observed. A significant increase in VEmax was demonstrated for II and DD genotypes, but not for ID heterozygotes. The greatest gain in power of countermovement jump was observed in II homozygotes, although DD and ID were associated with a significant increase as well. Our study indicated that the polymorphism was associated with changes in VEmax and power of countermovement jump in response to a 12-week aerobic training programme in Caucasian women. However, more experimental studies are needed to establish the ACE gene × physical activity interactions
Keywords: ACE I/D polymorphism; gene × physical activity interaction; training programme